2020
DOI: 10.1101/2020.07.06.189241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis clarifies the population genetic structure of wild Gilthead Sea Bream (Sparus aurata)

Abstract: AbstractGilthead sea bream is an important target for both recreational and commercial fishing in Europe, where it is also one of the most important cultured fish. Its distribution range goes from the Mediterranean to the African and European coasts of the North-East Atlantic. So far, the genetic structure of this species in the wild has been studied with microsatellite DNA, but the pattern of differentiation could not be fully clarified. In this study, almost 1000 wild sea bre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…In this case, wild populations were sampled from two regions, the Mediterranean and Atlantic. Wild individuals segregate into two closely bound Mediterranean and Atlantic clusters, which is consistent with previous findings indicating a low genetic differentiation between regions [ 58 , 59 ]. Similar to European seabass, a few wild individuals are found scattered throughout farmed populations, likely representing escapees from local fish farms.…”
Section: Discussionsupporting
confidence: 92%
“…In this case, wild populations were sampled from two regions, the Mediterranean and Atlantic. Wild individuals segregate into two closely bound Mediterranean and Atlantic clusters, which is consistent with previous findings indicating a low genetic differentiation between regions [ 58 , 59 ]. Similar to European seabass, a few wild individuals are found scattered throughout farmed populations, likely representing escapees from local fish farms.…”
Section: Discussionsupporting
confidence: 92%
“…In this case, wild populations were sampled from two regions, the Mediterranean and Atlantic. Wild individuals segregate into two closely bound Mediterranean and Atlantic clusters, which is consistent with previous findings indicating a low genetic differentiation between basins [51]. Similar to European seabass, a few wild individuals are found scattered throughout farmed populations, likely representing escapees from local fish farms.…”
Section: Population Structure and Haplotype Sharing Analysissupporting
confidence: 90%
“…Targeting outlier loci that often reflect divergent selection processes can offer a powerful way to study species with large population sizes, high dispersal capabilities and frequent geneflow leading to population homogenization (Milano et al, 2014;Tigano et al, 2017;Jenkins et al, 2019) and has proven to be a highly effective approach in cases where random sets of markers show little or no structure (Hollenbeck et al, 2019;Wilder et al, 2020;Maroso et al, 2021). Our two-step approach enabled comparison of two type of datasets to resolve population structuring for lumpfish.…”
Section: Two Datasets -Pitfalls and Advantagesmentioning
confidence: 99%
“…Genetic studies on marine fish have shown that, I) the effective population size reflecting population resilience may be only a fraction of the census size (Palstra and Ruzzante, 2008;Portnoy et al, 2008), II) the rate of effective migration might be lower than anticipated also in species with pelagic eggs and larvae (Spies et al, 2018), III) populations often encompass local adaptations (Van Wyngaarden et al, 2017;Gonçalves da Silva et al, 2019;Palumbi et al, 2019;Han et al, 2020), and that, IV) existing management units often misalign with population genetic structure and barriers to gene-flow (Reiss et al, 2009;Kerr et al, 2017;Quintela et al, 2020). Moreover, as populations are temporally and spatially dynamic entities, it is important that the status of species and their populations is monitored and regularly updated, especially when emerging methods and approaches can provide new insights (Hemmer-Hansen et al, 2019;Huret et al, 2020;Maroso et al, 2020;Xuereb et al, 2020;Hohenlohe et al, 2021). Lumpfish, Cyclopterus lumpus, is a cold-water marine species (Hvas et al, 2018) distributed throughout the North Atlantic (Davenport, 1985) (Figure 1) that has a long history of commercial exploitation.…”
Section: Introductionmentioning
confidence: 99%